Technoeconomic Conservation Voltage Reduction–Based Demand Response Approach to Control Distributed Power Networks - Shahram Pourfarzin; Tahere Daemi; Hamidreza Akbari (International Transactions on Electrical Energy Systems)
This manuscript investigates the transformative shift in electricity generation and distribution towards distributed power networks, particularly microgrids, amid escalating energy demand and environmental concerns. Emphasizing a pioneering technoeconomic conservation voltage reduction–based demand response approach, the study integrates conservation voltage reduction as a controllable demand response method within distributed power networks, highlighting the developed droop control method for effective regulation. Conservation voltage reduction, a no-cost procedure for minimizing loss, is applied to reduce voltage during peak periods to conserve power, decrease active and reactive power losses through precise load modeling, and enhance consumption efficiency. The most significant challenge of this project is the simultaneous use of conservation voltage reduction with the uncertainties of distributed generation sources, resulting to reduce losses and ultimately lower operating costs, a topic not previously studied in existing literature. The contributions include introducing a novel approach based on droop control to manage resources and presenting a detailed control strategy tailored to distributed power networks for improving voltage stability with minimal costs. Importantly, the proposed method demonstrates superior accuracy, achieving up to an 18% improvement over existing methods. This research contributes to comprehensive solutions for optimizing energy consumption, enhancing grid stability, and adapting to the evolving distributed power systems landscape.